Full-length sequence assembly reveals circular RNAs with diverse non-GT/AG splicing signals in rice. Issue 8 (3rd August 2017) - Ye, Chu-Yu; Zhang, Xingchen; Chu, Qinjie; Liu, Chen; Yu, Yongyi; Jiang, Weiqin; Zhu, Qian-Hao; Fan, Longjiang; Guo, Longbiao
ABSTRACT: Circular RNAs (circRNAs) have been identified in diverse eukaryotic species and are characterized by RNA backsplicing events. Current available methods for circRNA identification are able to determine the start and end locations of circRNAs in the genome but not their full-length sequences. In this study, we developed a method to assemble the full-length sequences of circRNAs using the backsplicing RNA-Seq reads and their corresponding paired-end reads. By applying the method to an rRNA-depleted/RNase R-treated RNA-Seq dataset, we for the first time identified full-length sequences of nearly 3, 000 circRNAs in rice. We further showed that alternative circularization of circRNA is a common feature in rice and, surprisingly, found that the junction sites of a large number of rice circRNAs are flanked by diverse non-GT/AG splicing signals while most human exonic circRNAs are flanked by canonical GT/AG splicing signals. Our study provides a method for genome-wide identification of full-length circRNAs and expands our understanding of splicing signals of circRNAs.